Submission of a Civil Suit by a Prosecutor in the Interests of a State as a Way of Compensation for Damage, Caused by a Criminal Offence - Brusakova, Oksana Valeriivna; Shayturo, Olga Pavlivna; Simonovych, Davyd; Kuzubova, Tetiana (Jurnal Cita Hukum, 2021)
The outcome of every trial is always accompanied by some interest where the civil attains compensation and the criminal imprisonment and fines. In achieving the said interest in a trial process, it is the role of the prosecutor in establishing that the accused is guilty of the crime committed. This article articulates, that it is the role of the prosecutor to carry out justice in the name of the State whether during the criminal or civil trial. The principle is clear here as we all know that during criminal proceedings the prosecutor is the principal party, but such a trial cannot succeed if in the course of the criminal act the victim also incurred damages caused by the accused. In this regard, it is also the role of the prosecuting counsel to submit such a civil action that has caused damages to the victim. There are lots of complexities surrounding the understanding and interpretation of the word "interest of the state" as many states fail in establishing this in their various legislation in which the state of Ukraine is not an exception. Notwithstanding the importance of this concept in every trial whether civil or criminal, what becomes of its outcome when effective recognition is not attached to it in terms of legislative recognition? It is there in this safeguard that there was a necessity in examining the place occupied by the submission of civil suits for the interest of the state and its implications in matters related to damages was deemed necessary.Keywords: Powers; Prosecutor's Office; Civil Lawsuit; Legal Guarantees; Procedural Order; Temporary Withdrawal; Arrest of PropertyPengajuan Gugatan Perdata oleh Penuntut untuk Kepentingan Negara Sebagai Cara Ganti Kerugian Akibat Tindak Pidana AbstrakHasil dari setiap persidangan selalu disertai dengan beberapa kepentingan, di mana perdata memperoleh kompensasi, dan pidana penjara dan denda. Dalam mencapai kepentingan tersebut dalam proses persidangan, adalah peran jaksa dalam menetapkan bahwa terdakwa bersalah atas kejahatan yang dilakukan. Pasal ini mengartikulasikan, bahwa adalah peran kejaksaan untuk menegakkan keadilan atas nama negara baik dalam persidangan pidana maupun perdata. Prinsipnya jelas di sini seperti yang kita ketahui bersama bahwa dalam proses pidana jaksa adalah pihak utama, tetapi persidangan seperti itu tidak dapat berhasil jika dalam tindak pidana korban juga mengalami kerugian yang disebabkan oleh terdakwa. Berkenaan dengan itu, juga peran jaksa penuntut untuk mengajukan gugatan perdata yang telah menimbulkan kerugian bagi korban. Ada banyak kerumitan seputar pemahaman dan interpretasi kata "kepentingan negara" karena banyak negara gagal menetapkan ini dalam berbagai undang-undang mereka di mana negara Ukraina tidak terkecuali. Terlepas dari pentingnya konsep ini dalam setiap persidangan baik perdata maupun pidana, apa jadinya jika pengakuan yang efektif tidak dilampirkan padanya dalam hal pengakuan legislatif? Dalam pengamanan ini perlu dilakukan pemeriksaan terhadap tempat yang ditempati oleh pengajuan gugatan perdata untuk kepentingan negara dan implikasinya dalam hal-hal yang berkaitan dengan kerugian dianggap perlu.Kata Kunci: Kekuasaan; Kejaksaan; Gugatan Perdata; Jaminan Hukum; Tata Cara; Penarikan Sementara; Penangkapan Properti Подача прокурором гражданского иска в интересах государства как способ возмещения вреда причиненного уголовным преступлением АннотацияРезультат каждого судебного разбирательства всегда сопровождается определенным интересом, когда гражданское лицо получает уголовное заключение или штраф. В достижении указанного интереса в судебном процессе прокурор должен установить, что обвиняемый виновен в совершенном преступлении. В этой статье говорится, что деятельность прокурора осуществляется от имени государства, будь то во время уголовного или гражданского судопроизводства. Принцип здесь ясен, поскольку все мы знаем, что во время уголовного разбирательства прокурор является стороной обвинения, но судебное разбирательство может быть успешным, если ущерб, понесенный государством, будет возмещен обвиняемым. В этом отношении роль прокурора также состоит в том, чтобы подать гражданском иск, который является одним из наиболее эффективных способов возмещения вреда, причиненного уголовным преступлением. Есть много сложностей, связанных с пониманием и толкованием слова «заинтересованность государства», поскольку многие государства не могут это установить на уровне закона. Несмотря на важность этой концепции, эффективность возмещение вреда, причиненного государству, остается на низком уровне. Именно поэтому возникла необходимость в изучении места гражданского иска прокурора, как гарантии защиты интересов государства, а также определения его значения в вопросах, связанных с возмещением ущерба, причиненного уголовным правонарушением.Ключевые слова: полномочия, прокуратура, гражданский иск, правовые гарантии, процессуальный порядок, временное изъятие, арест имущества.